THE USE OF JIGSAW TECHNIQUE IN IMPROVING STUDENTS’ READING SKILL ON NARRATIVE TEXT - Tannaya Cahyaningtyas Wiyono; Hasti Robiasih (JELLT (Journal of English Language and Language Teaching), 2019)
Reading skill becomes one of the skills that should be mastered by students. The students needs to know how to read an English text in order to develop their potential in learning. To achieve the goal, it is necessary to have techniques that can help students to read well. One of the technique that can be used is Jigsaw technique. The objectives of this study are: 1) to describe the implementation of using Jigsaw technique in improving students’ reading skill on the narrative text of ninth grade of Kejar Paket B in PKBM Sejahtera Yogyakarta, and 2) to describe the result of the implementation. This research was a classroom action research which consisted of two cycles. The results of cycle 1 were: 1) the students were motivated to learn during the lesson, 2) the students enjoyed the learning process using the Jigsaw technique. The results of cycle 2 were: 1) the students were more motivated in showing their effort to study. 2) the students were more active in discussing the generic structure, the main idea, and the topic of the text. The strategy was helpful in teaching narrative text. It could make the students got motivated to read the text and active during the discussion.